BOOSTER NIRA KELAPA MIX JERUK BRASTAGI DAN METODE AMENORHOE LAKTASI KETERKAITANNYA DENGAN PRODUKSI ASI - Surya Anita; Julia Siahaan; Christina Roos Etty Nainggolan (LPPM Universitas Abdurrab, 2026)
Early breastfeeding is highly recommended because it provides many health benefits for both mother and baby. From birth, babies are equipped with life reflexes to sustain their lives. Within the first hour, babies will learn to breastfeed or get used to sucking on the nipple, preparing the mother to start producing colostrum. Unrestricted access to mother-baby bonding and unlimited breastfeeding frequency in the first few days after delivery are crucial for ensuring adequate breast milk supply for the baby. Exclusive breastfeeding coverage in Indonesia is still at 54.3%, while the target for 2024 is 80%. In North Sumatra, exclusive breastfeeding coverage in 2024 is still at 66.42%. This study is a quasi-experimental quantitative study using a case-control approach, which aims to test the effectiveness of a coconut milk breast milk booster mixed with Brastagi orange, which is a local food product from North Sumatra. The results of this study indicate that there is a significant relationship between the administration of coconut sap mixed with Brastagi orange breast milk booster and the application of the Lactational Amenorrhea Method (LAM) on increasing breast milk production in postpartum mothers. The Chi-square test shows a value of p = 0.013, which means that the relationship between the intervention and breast milk production is statistically significant (p < 0.05). The Odds Ratio (OR) value of 0.10 indicates that postpartum mothers who were given the coconut sap mixed with Brastagi orange booster had a lower risk of low breast milk production compared to those who did not receive the booster.